MUSHROOM FARMER'S DILEMMA: MARKET DEPENDENCE AND ENVIRONMENTAL POLLUTION THREAT - Adi, Angga Prasetyo (Jurnal Partisipatoris, 2019)
In critical reviews on here I write under the title dilemma mushroom growers to the pressures of globalization and capitalist sheath through ecotourism which resulted in the pollution of the environment. In this article use using work unpaid are pointed Alvin A Camba (2018) which describes the regime of food in the colonial period in the Philippines in the article here I try mengabtraksi dilemma mushroom growers area of jungle fighting that produce mushrooms worth matrial is quite high but it is also the existence of a environmental threats due to fighting forest used as a tourism icon for Bangka middle that invites tourists to enter and threaten the environment with the waste that was taken. Because ecotourism managers who are fighting the forest does not have the tools for waste management, but it is also packing systems made by managers who are still using plastic that will keep growing volume of plastic waste. Mushroom packing pattern which will be marketed through the jungle fighting travel does not have the technology to avoid the use of plastics. Keyword: food regime, environmental sociology, ecology economy